The ideal light source for datanets. - Giboney, K.S.
The appetite for ever increasing computing power and interconnection bandwidth could be sated by vertical-cavity, surface-emitting lasers (VCSEL) for optical data communication. Made inexpensively using IC processing techniques, they can be diced in planar or linear arrays, such as in the wavelength-division multiplexer. The author discusses the essentials of semiconductor light sources, epitaxial growth of the surface-emitting laser and its interior design. The characteristics and operation of the VCSEL are described
Keywords: IC processing techniques; Computing power; Data networks; Epitaxial growth; Interconnection bandwidth; Interior laser design; Linear arrays; Optical data communication; Planar arrays; Semiconductor light sources; Vertical-cavity surface-emitting lasers; Wavelength-division multiplexer